Full-text retrievals and EBSCO Discovery Service: Assessing usage of e-journals across multiple platforms. Issue 2 (24th June 2022) - Robins, Simon
Abstract: This study utilizes COUNTER 5 data from the University of Dayton (UD) to measure full-text retrievals of e-journal articles from five major academic journal publishers (Taylor & Francis, SAGE, Oxford, Wiley, and Springer). Usage data from these publishers' e-journals within EBSCO is compared to the same content when accessed from publisher platforms such as Wiley Online Library or SpringerLINK. Building on previous studies that have largely focused on links (or referrals) from the library discovery layer to publisher platforms, this study analyzes usage of full text-articles stored within EBSCO Discovery Service and EBSCOhost subject databases to consider how these full-text holdings within EBSCO might affect referrals to publisher platforms. The findings indicate that full-text article holdings within EBSCO are used more often than the same content in publisher platforms, suggesting that UD students and researchers rely heavily on—and likely often start with—EBSCO for their learning and research.